When Work Disappears: Manufacturing Decline and the Falling Marriage-Market Value of Young Men - David Autor; David Dorn; Gordon H. Hanson (Institute of Labor Economics (IZA), 2018)
We exploit the gender-specific components of large-scale labor demand shocks stemming from rising international manufacturing competition to test how shifts in the relative economic stature of young men versus young women affected marriage, fertility and children's living circumstances during 1990-2014. On average, trade shocks differentially reduce employment and earnings of young adult males. Consistent with Becker's model of household specialization, shocks to male's relative earnings reduce marriage and fertility. Consistent with prominent sociological accounts, these shocks heighten male idleness and premature mortality, and raise the share of mothers who are unwed and the share of children living in below-poverty, single-headed households.
Keywords: F16; J12; J13; J21; J23; 330; import competition; trade flows; single-parent families; household structure; mortality; fertility; marriage market; local labor markets